2018
DOI: 10.3892/mmr.2018.9724
|View full text |Cite
|
Sign up to set email alerts
|

Chrysin protects human osteoarthritis chondrocytes by inhibiting inflammatory mediator expression via HMGB1 suppression

Abstract: High-mobility group box chromosomal protein (HMGB-1) contributes to osteoarthritis (OA) by modulating various oxidative, inflammatory and apoptotic signaling pathways. The effect of chrysin (CH), a natural plant flavonoid, and its functional interaction with HMGB-1, was investigated in a chondrocyte model of OA. Human chondrocytes were pre-treated with CH, and then subsequently treated with IL-1β to induce the formation of chondrocytes similar to those found in OA joints. Next, the expression level of HMGB-1 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 39 publications
(40 reference statements)
0
17
0
1
Order By: Relevance
“…14 In this study, we have investigated the anti-cancer effects of Chrysin against GC cells both in vitro and in vivo and our data suggested that Chrysin exerted significant anti-tumor capabilities including enhanced cell apoptosis, cell cycle arrest, increased cell migration, and invasion in GC cells which further supported our previous findings in melanoma 15 cells and osteoarthritis chondrocytes. 16 Recently, studies have indicated that Chrysin exhibited the ability to regulate gene expression of hTERT in breast cancer. 17 Moreover, Chrysin could regulate MMP-9 expression in GC.…”
Section: Discussionmentioning
confidence: 99%
“…14 In this study, we have investigated the anti-cancer effects of Chrysin against GC cells both in vitro and in vivo and our data suggested that Chrysin exerted significant anti-tumor capabilities including enhanced cell apoptosis, cell cycle arrest, increased cell migration, and invasion in GC cells which further supported our previous findings in melanoma 15 cells and osteoarthritis chondrocytes. 16 Recently, studies have indicated that Chrysin exhibited the ability to regulate gene expression of hTERT in breast cancer. 17 Moreover, Chrysin could regulate MMP-9 expression in GC.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory reactions in synovial tissues are accompanied by congestion, edema, the accumulation of inflammatory mediators and the secretion of various types of proteases, ultimately resulting in abnormal cartilage metabolism (36,37). FLSs are important factors in KOA inflammation and joint destruction during the pathological progression of Koa, primarily by secreting a wide range of proinflammatory mediators, such as il-1β, il-18, TnF-α and MMPs (38). HMGB1 has been reported to serve a proinflammatory role in KOA (23,26), and HMGB1 levels in synovial fluid are closely associated with the severity of Koa (39).…”
Section: Discussionmentioning
confidence: 99%
“…HMGB1 has been previously studied in OA; it is highly expressed in the articular cartilage and synovium and plays an important role in the process of KOA (15,16). However, the specific mechanism underlying the activity of HMGB1 in KOA has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%